PREVENTION OF OVARIAN, FALLOPIAN TUBE, AND PERITONEAL SEROUS CANCERS (LITERATURE REVIEW) - Sumtsov, Dmytro (Eastern Ukrainian Medical Journal, 2024)
Introduction. This literature review presents an analysis of the incidence and state of prevention of highly malignant tumors that are difficult to diagnose: serous ovarian cancer, primary fallopian tube cancer, and primary peritoneal cancer. In this group of patients, ovarian cancer amounts to 82.0%, fallopian tube cancer – 6.4%, and peritoneal cancer – 10.7%. The problem is very urgent, since, according to the International Agency for Research on Cancer (IARC), more than 225,000 new cases of ovarian cancer alone are registered annually in the world, and more than half of the patients die during the year. No more than 30% of the treated patients survive for up to 10 years. Such poor results are due to the lack of effective methods of prevention and the difficulties of diagnosing this group of diseases. Methods. The author selected from the world literature more than 45 scientific works on the problems of incidence and prevention of ovarian cancer, primary fallopian tube cancer, and peritoneal cancer and carried out a detailed analysis of them. Results and Discussion. At the beginning of the 21st century, after a number of morphological, immunohistochemical, and molecular genetic examinations, the global scientific community clearly proved that the root cause of serous ovarian, fallopian tube, and peritoneal cancers is the pathology of the fallopian tube mucosa. Practical observations revealed that women who underwent salpingectomy or tubal sterilization had a much lower risk of serous pelvic cancers. As a result of these examinations and observations, clinical recommendations were made: in order to prevent ovarian cancer, women should be suggested opportunistic bilateral salpingectomy during their operations in the post-reproductive age. Sterilization should be done by removing the fallopian tubes, not by ligation, because of the lower efficiency of the latter. According to the reports of some authors, this method can reduce the risk of ovarian cancer by 90–98%. There is a lack of reports on the prevention of fallopian tube and peritoneal cancers in the periodical scientific literature, but we can assume that they will not be worse than those for ovarian cancer.